Living in-between: children of immigrants in the urban space - Granata, Anna; Granata, Elena (Rivista Italiana di Educazione Familiare, 2016)
Family and school are not the only educational agencies in daily life of new generations. In this paper, we argue that the city itself can be regarded as well as a great educational agency where an extraordinarily important formative experience takes place. This paper is aimed at exploring the experience of urban space as one of the main components of the process of growth and integration of children of immigrants. This is an experience which takes place in relationships in between indoors (home and school) outdoors (urban context and digital world) spaces, and in between different codes and meanings. This perspective of research aims to investigate the role of urban and digital settings in encouraging or discouraging social integration processes in Italy. The Authors have analysed it through qualitative researches, in between educational studies and urban policies.